Effect of Puffing Behavior on Particle Size Distributions and Respiratory Depositions From Pod-Style Electronic Cigarette, or Vaping, Products - Ranpara, Anand; Stefaniak, Aleksandr B.; Fernandez, Elizabeth; LeBouf, Ryan F. (Frontiers in Public Health, 2021)
Current, fourth generation (‘pod-style’) electronic cigarette, or vaping, products (EVPs) heat a liquid (‘e-liquid’) contained in a reservoir (‘pod’) using a battery-powered coil to deliver aerosol into the lungs. A portion of inhaled EVPs aerosol is estimated as exhaled, which can present a potential secondhand exposure risk to bystanders. The effects of modifiable factors using either a pre-filled disposable or refillable pod-style EVPs on aerosol particle size distribution (PSD) and their respiratory deposition are poorly understood. In this study, the influence of up to six puff profiles (55, 65, and 75 milliliters (mL) puff volumes per 6.5 and 7.5 Watts (W) EVPs power settings) on PSD was evaluated using a popular pod-style EVPs (JUUL® brand) and a cascade impactor. JUUL® brand EVPs was used to aerosolize the manufacturers e-liquids in their disposable pods and laboratory prepared “reference e-liquid” (without flavorings or nicotine) in refillable pods. The modelled dosimetry and calculated aerosol mass median aerodynamic diameters (MMADs) were used to estimate regional respiratory deposition. From these results, exhaled fraction of EVPs aerosols was calculated as a surrogate of secondhand exposure potential. Overall, MMADs did not differ among puff profiles, except for 55- and 75-mL volumes at 7.5W (p<0.05). For the reference e-liquid, MMADs ranged from 1.02 to 1.23 micrometers (µm) and dosimetry calculations predicted that particles would deposit in the head region (36%–41%), trachea-bronchial region (19%–21%) and in the pulmonary region (40%–43%). For commercial JUUL® e-liquids, MMADs ranged from 0.92 to 1.67 µm and modelling predicted that more particles would deposit in the head region (35%–52%) and in the pulmonary region (30%–42%). Overall, 30%–40% of particles aerosolized by a pod-style EVPs were estimated to deposit in the pulmonary region and 50%–70% of inhaled EVPs aerosols could be exhaled; the latter could present an inhalational hazard to bystanders in indoor occupational settings. More research is needed to understand the influence of other modifiable factors on PSD and exposure potential.